The Thousand-Pulsar-Array programme on MeerKAT – XI. Application of the rotating vector model. Issue 4 (27th February 2023) - Johnston, S; Kramer, M; Karastergiou, A; Keith, M J; Oswald, L S; Parthasarathy, A; Weltevrede, P
ABSTRACT: In spite of the rich phenomenology of the polarization properties of radio pulsars, the rotating vector model (RVM) created 50 years ago remains the best method to determine the beam geometry of a pulsar. We apply the RVM to a sample of 854 radio pulsars observed with the MeerKAT telescope in order to draw conclusions about the population of pulsars as a whole. The main results are that (i) the geometrical interpretation of the position angle (PA) traverse is valid in the majority of the population, (ii) the pulsars for which the RVM fails tend to have a high fraction of circular polarization compared to linear polarization, (iii) emission heights obtained through both geometrical and relativistic methods show that the majority of pulsars must have emission heights less than 1000 km independent of the spin period, (iv) orthogonal mode jumps are seen in the PA traverse in about one third of the population. All these results are weakly dependent on the pulsar spin-down energy.